2007
DOI: 10.1002/pip.765
|View full text |Cite
|
Sign up to set email alerts
|

8% Efficient thin‐film polycrystalline‐silicon solar cells based on aluminum‐ induced crystallization and thermal CVD

Abstract: A considerable cost reduction could be achieved in photovoltaics if efficient solar cells could be made from polycrystalline‐silicon (pc‐Si) thin films on inexpensive substrates. We recently showed promising solar cell results using pc‐Si layers obtained by aluminum‐induced crystallization (AIC) of amorphous silicon in combination with thermal chemical vapor deposition (CVD). To obtain highly efficient pc‐Si solar cells, however, the material quality has to be optimized and cell processes different from those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 14 publications
0
71
1
1
Order By: Relevance
“…[8][9][10][11] An approach where the deposition is done at temperatures of about 1100 8C shows promising results, but requires substrates capable of withstanding these temperatures. [12] Processes using lower deposition temperatures are attractive since they are compatible with the usage of glass substrates. The most prominent low temperature technique is based on solid phase crystallization (SPC) of amorphous Si films that are deposited by either chemical (CVD) [7] or physical vapour deposition (PVD) processes.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] An approach where the deposition is done at temperatures of about 1100 8C shows promising results, but requires substrates capable of withstanding these temperatures. [12] Processes using lower deposition temperatures are attractive since they are compatible with the usage of glass substrates. The most prominent low temperature technique is based on solid phase crystallization (SPC) of amorphous Si films that are deposited by either chemical (CVD) [7] or physical vapour deposition (PVD) processes.…”
Section: Introductionmentioning
confidence: 99%
“…Rech et al showed that ZnO:Al films prepared by magnetron sputtering and post deposition wet chemical etching demonstrate an effective light trapping and the textured surface reduces reflection losses at the ZnO:Al/Si-interface with excellent light scattering properties for silicon thin film solar cells and modules [3,4]. Grained polycrystalline silicon (poly-Si) films were prepared on nano-textured glass substrates by epitaxial thickening of seed layers formed by the aluminum-induced layer exchange (ALILE) process [5,6] for poly-Si thin film solar cell application with 8% efficiencies with improved material quality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Large grains p-type pc-Si can be obtained by aluminum induced crystallization (AIC) [7]. Thin-film polycrystalline-silicon solar cells based on AIC and thermal CVD with 8% efficiency has already been reported on alumina substrate [8].…”
Section: Introductionmentioning
confidence: 99%